A Hybrid Viscosity Approximation Method for a Common Solution of a General System of Variational Inequalities, an Equilibrium Problem, and Fixed Point Problems (Journal of Computational Mathematics, 2022)
In this paper, we introduce a new iterative method based on the hybrid viscosity approximation method for finding a common element of the set of solutions of a general system of variational inequalities, an equilibrium problem, and the set of common fixed points of a countable family of nonexpansive mappings in a Hilbert space. We prove a strong convergence theorem of the proposed iterative scheme under some suitable conditions on the parameters. Furthermore, we apply our main result for W-mappings. Finally, we give two numerical results to show the consistency and accuracy of the scheme.